Personal Data Protection Awareness through the Use of YouTube among the Youths in UUM - Mohamad Fadli Zolkipli; Diviya Shini Rajamanickam (Pejabat Karang Mengarang UPSI, 2021)
This paper is to discuss the awareness among the youth in UUM related to personal data protection. The cases of personal data protection increased day by day among the youths. Several awareness programs were done. The purpose of this study was to raise awareness of the importance of protecting personal data among the youth in Universiti Utara Malaysia. The method used to do awareness programs by using YouTube and online surveys. Awareness program using YouTube is highly recommended. The finding reveals that it can use this type of media to conduct awareness programs.